Optical temperature sensing properties and thermoluminescence behavior in Er-modified potassium sodium niobate-based multifunctional ferroelectric ceramics. Issue 33 (28th June 2022) - Li, Wei; Wang, Di; Li, Xuefeng; Li, Peng; Fu, Peng; Hu, Chengchao; Hao, Jigong; Li, Wei; Zhang, Qiwei
Abstract : Er 3+ -doped KNN-based ceramics exhibited multifunctional features with upconversion luminescence, thermoluminescence, and ferroelectric/piezoelectric properties, which may enable novel applications in the field of optoelectronic devices. Abstract : The use of multifunctional materials that exhibit integration/coupling effects among different properties has recently become the research hotspot with the development of a high-tech optoelectronic technology. In this work, we report the multifunctional characteristics with upconversion luminescence, thermoluminescence, and ferroelectric properties of potassium sodium niobate (KNN)-based ferroelectric ceramics. A host KNN-based material was constructed using Er 3+ regulation, boosting the electrical properties and activating the luminescence properties of the host. After Er 3+ doping, the ceramics exhibited fatigue-resistant and temperature-insensitive ferroelectric/strain properties. Moreover, the Er 3+ -modified samples showed bright upconversion photoluminescence, simultaneously exhibiting thermoluminescence behavior. High-temperature sensing with a sensitivity of S = 0.0061 K −1 was achieved in the sample doped with 0.5%mol Er 3+ . In addition, thermoluminescence behavior was observed in this sample, closely related to the concentration of defects inside the ceramics. As multifunctional materials, Er 3+ -doped KNN-based ferroelectrics may enable novel applications in the field of optoelectronic devices.